Satellite hyperspectral remote sensing for estimating estuarine and coastal water quality - Brando, V.E.; Dekker, A.G. (IEEE transactions on geoscience and remote sensing, 2003)
The successful launch of Hyperion in November 2000 bridged the gap between the high-resolution (spatial and spectral) airborne remote sensing and the lower resolution satellite remote sensing. Although designed as a technical demonstration for land applications, Hyperion was tested for its capabilities over a range of water targets in Eastern Australia, including Moreton Bay in southern Queensland. Moreton Bay was the only Australian Earth Observing 1 (EO-1) Hyperion coastal site used for calibration/validation activities. This region was selected due to its spatial gradients in optical depth, water quality, bathymetry, and substrate composition. A combination of turbid and humic river inputs, as well as the open ocean flushing, determines the water quality of the bay. The field campaigns were coincident with Hyperion overpasses, retrieved inherent optical properties, apparent optical properties, substrate reflectance spectra, and water quality parameters. Environmental noise calculations demonstrate that Hyperion has sufficient sensitivity to detect optical water quality concentrations of colored dissolved organic matter, chlorophyll, and suspended matter in the complex waters of Moreton Bay. A methodology was developed integrating atmospheric and hydrooptical radiative transfer models (MODTRAN-4, Hydrolight) to estimate the underwater light field. A matrix inversion method was applied to retrieve concentrations of chlorophyll, colored dissolved organic matter, and suspended matter, which were comparable to those estimated in the field on the days of the overpass.